Comparative Analysis of Different Insecticides Against Thrip (Thrips Tabaci) on Cotton Crop (Journal of Agriculture and Biology, 2025)
Cotton (Gossypium hirsutum L.) is the significant cash crop and produces the fiber-based yield throughout the world. As several as types of insect pests have been attacked on cotton crop among them cotton thrip (Thrips tabaci) cause huge losses by suck the cell sap of leaves and reduce the yield every year. Selective insecticide chemicals are the dire need nowadays to manage cotton thrip, because of their target oriented and immediate knockdown effect. Farmers still depend on old chemistry-based insecticides for controlling the thrip pest which is not work properly, thus the present research was initiated to determine the effectiveness of novel insecticides against cotton thrip. Results showed the after first spray overall average of various time intervals that maximum mortality % was recorded from the plots which treated with Ulala insecticide such as such as (70.02±10.05%) followed by Acephate insecticide (59.79±07.00%) and Mospilan insecticide (53.04±08.19%), and Polo (48.82±08.06%) respectively. However, after the application of second spray highest mortality % was recorded from the plots which treated with Ulala insecticide such as (64.09±09.09%) by Acephate insecticide (61.17±07.10%) and Mospilan insecticide (47.62±08.05), and Polo (38.59±08.96%) respectively. Further, yield of cotton after the applications of different insecticides was recorded and maximum yield was obtained from the plots which traded with Ulala chemical such as (769.30 kg/acre) followed by Acephate chemical (739.66 kg/acre), Mospilan chemical (712.00 kg/acre), Polo chemical (673.0 kg/acre) and Control untreated (625.0), respectively. In addition, yield over control was also computed and maximum (178.00 kg/acre) was obtained from the plots which treated with Ulala insecticide followed by Acephate (114.25 kg/ acre), Mospilan insecticide (86.65 kg/acre), Polo (673.00 kg/acre) as compared to control. Based on the results, it is recommended that Ulala and Acephate insecticide product should be sprayed on cotton crop under field for the management cotton thrip for the less crop infestation and better cotton production.